High-Speed Reconciliation for CVQKD Based on Spatially Coupled LDPC Codes - Xue-Qin Jiang; Siyuan Yang; Peng Huang; Guihua Zeng (IEEE Photonics Journal)
The speed of continuous variable quantum key distribution is limited by the reconciliation efficiency and the reconciliation frame error rate (FER) in the reconciliation phase. In this paper, we propose an approach that may increase the reconciliation efficiency and decrease the FER. In detail, to increase the reconciliation efficiency, rather than using the block low-density parity-check (LDPC) codes, such as quasi-cyclic LDPC codes, multiedge-type LDPC codes, and punctured LDPC codes, this paper introduces spatially coupled (SC) LDPC codes to the reconciliation phase. To decrease the FER, we propose a new reconciliation scheme based on the special structure of SC-LDPC codes. To demonstrate the performance of the proposed approach, we construct the SC-LDPC codes based on quasi-cyclic repeat-accumulate codes. It is shown that the proposed scheme leads to higher reconciliation speed than that of the previous reconciliation schemes.